58.6k views
0 votes
C^4 - c^3 - 2c^2 - 2c = 0Help please!!

C^4 - c^3 - 2c^2 - 2c = 0Help please!!-example-1
User Oya Canli
by
5.2k points

1 Answer

3 votes

Problem


C^4-C^3-2C^2\text{ + 2C = 0}

Step 1: Factor C out of the equation, we get:


C(C^3-C^2\text{ - 2C + 2) = 0}

Step 2: factor the expression in the bracket


C^3-C^2\text{ - 2C + 2 = 0}

From the expression above, find the first zero. C = 1 is a zero of the expression because C - 1 is a factor.

Therefore


undefined

C^4 - c^3 - 2c^2 - 2c = 0Help please!!-example-1
User DAB
by
5.6k points